A Morphological Analysis of Diadem Roundleaf Bat (Hipposideridae , Hipposideros Diadema) in Malaysia - Nurshilawati, Abdul Latip (Universiti Malaysia Sarawak, UNIMAS, 2013)
The morphological study was carried out to record and analyse the morphological characters of H. diadema from four different populations in Malaysia (Peninsular Malaysia, South and North Sarawak, Sabah). Nine external, 17 craniodental characters were measured and analysed using the multivariate analysis and discriminant function analysis (DFA) using the SPSS Version 20.0 software. Cluster analysis was done using Paleontological Statistic (PAST) version 2.17. The external and craniodental characters were analysed separately. For external character, the highest character loading for both Function 1 and 2 was forearm (FA), whereas for Function 3 it was tibia (TL). For internal character, the highest character loading for Function 1, 2, and 3 were great skull length (GSL), palatal length (PL), and postpalatal length (PPL). These internal characters are cranial characters which two of them are related to palatal length. These findings establish the morphological variation between four geographically separate populations of H. diadema within Malaysia.